PERANAN MEDIA PEMBELAJARAN VIDEO ANIMASI DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PPKn KELAS XI SMA SWASTA ERIA MEDAN TAHUN PELAJARAN 2025/2026 - Pingky, Pingky Monica Hasugian; Liber, Liber Siagian; Jamaluddin, Jamaluddin; Sri Yunita, Sri Yunita; Oksari , Oksari Anastasya Sihaloho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine how the role of animated video learning media can increase students' interest in learning PPKn subjects in grade XI of Eria Medan Private High School in the 2025/2026 Academic Year. This study uses a Descriptive Approach with qualitative methods. This research was conducted at Eria Medan Private High School, located at Jl. Sisingamangarajar No. 195, Medan Kota District, Medan City, North Sumatra. The research subjects consisted of 1 PPKn Teacher and 8 Grade XI Students. The data collected included primary data from documentation, interviews and observations. And secondary data from books, journals and relevant internet websites. Data collection techniques involved observation, interviews and documentation. While data analysis techniques included data reduction, data display and data verification. The results of the study showed that the use of animated video learning media can attract students' attention, facilitate understanding of the material and increase students' learning motivation. Then a student's interest in learning can be seen from feelings of pleasure towards learning activities, high attention to learning, interest in the material being studied and active participation in learning activities. Therefore, it can be concluded that animated video learning media can increase students' interest in learning PPKn. Therefore, animated video learning media can be a real solution to the problem of low student interest in PPKn.